Examining Village Financial Accountability from the Perspective of Civil Service Competency and Management Systems: A Systematic Literature Review - Nabila Khairunnisa Ahmad Nabila; Maria Bianca Cheravin Maria; Afifah Alya Zulaikha Afifah; Novi Karsa Pratiwi Novi; Rika Henda Safitri Rika (Ekasakti Pareso Jurnal Akuntansi, 2026)
Fund allocations often increase as needs grow, and village management demands greater accountability due to these increased allocations. However, there are gaps in the competence of village officials and in system optimization that need to be addressed. This study employs a Systematic Literature Review method, analyzing 15 prior articles from the 2020–2025 period. The findings indicate that consistent improvements in the application of accounting standards and relatively rapid reporting can be achieved through the practical implementation of the Village Financial System (SISKEUDES). Financial literacy and moral integrity are the primary determining factors that can fulfill the accountability process as a means of ensuring the quality of informative information. Some reports still face technical challenges in achieving transparency, which poses a barrier within the scope of public accessibility. Thus, to realize village finances with high accountability, two main components that are well correlated are required: the intellectual strengthening of village officials and the massive utilization of technology. This study can indirectly contribute to decision-making regarding digital transformation efforts in rural areas.